Towards an International Political Economy of Artificial Intelligence
XVII, 258 p. 9 illus., 8 illus. in color.
Keywords: This book seeks to leverage academic interdisciplinarity to develop insight into how artificial intelligence (AI), the latest GPT to emerge, may influence or radically change socio-political norms, practices, and institutions. AI may best be understood as a predictive technology. “Prediction is the process of filling in missing information. Prediction takes information you have, often called ‘data’, and uses it to generate information you don’t have” (Agrawal, Gans, and Goldfarb 2018, 13; also see Mayer-Schonberger and Ramge 2018). AI makes prediction cheap because the cost of information is now close to zero. Cheap prediction through AI technologies is radically altering how we govern ourselves, interact with each other, and sustain society. Contributors to this book represent the academic disciplines of sociology and political science working within a diverse set of intra-disciplinary fields that when combined, yield novel insights into the following questions guiding this book: How might AI transform people? How might AI transform socio-political practices? How might AI transform socio-political institutions? Tugrul Keskin is Professor in the College of Liberal Arts and Director of the Centre for Global Governance at Shanghai University. Ryan Kiggins is Instructor in the Department of Political Science at the University of Central Oklahoma, Edmond, OK, USA.